Characterizing the interindividual postexercise hypotension response for two order groups of concurrent training in patients with morbid obesity - Álvarez, Cristian; Guede-Rojas, Francisco; Ramírez-Campillo, Rodrigo; Andrade, David C.; Vásquez-Gómez, Jaime; Rodríguez-Rodríguez, Fernando; Ciolac, Emmanuel Gomes; Caamaño-Navarrete, Felipe; Delgado-Floody, Pedro (Frontiers in Physiology, 2022)
Background: Postexercise hypotension (PEH) is a common physiological phenomenom occurring immediately after endurance (ET), resistance training (RT), and ET plus RT, also termed concurrent training (CT), however, there is little knowledge about the inter-individual and magnitude response of PEH in morbidly obesity patients. Aim: The aim of this study were (1) to investigate the effect of CT order (ET+RT vs. RT+ET) in the magnitude of PEH; (2) to charactyerize PEH responders and nonresponders; and (3) to identify potential baseline outcomes for predicting PEH responders. Methods: A quasi-experimental study developed in sedentary morbidly obesity men and women (age 43.6±11.3 y; body mass index [BMI] ≥40 kg/m2) were assigned to a CT group of ET plus RT (ET+RT; n=19; BMI 47.8±16.7) or to a RT plus ET group (RT+ET; n=17; BMI 43.0±8.0). Subjects of both groups received during 4-weeks (8-exercise sessions) systolic (SBP), diastolic (DBP), mean arterial pressure [MAP], heart rate at rest [HR], and pulse pressure [PP] measurements before and after 10 min postexercise. Secondary outcomes were other anthopometric, body composition, metabolic, and physical condition parameters. Using the ∆SBP reduction, and quartile categorization (Q) in ‘high’ (Rs: quartile 4), ‘moderate’ (MRs: quartile 3), ‘low’ (LRs: quartile 2), and ‘nonresponders’ (NRs: quartile 1) were reported. Results: No significant differences in the PEH between groups were detected in the summatory of the 4-weeks measurements at SBP (i.e., ∑∆SBP). Inter-individual analyses revealed significant differences among frequencies comparing Q1 ‘NRs’ (n=8; 22.2%), Q2 ‘LRs’ (n=8; 22.2%), Q3 ‘MRs’ (n=9; 25.0%), and Q4 ‘HRs’ (n=11; 30.5%), p<0.0001. Quartile comparisons showed significant differences in SBP (p=0.035). Linear regression analyses, revealed significant association between SBP decreases with body fat % (β –3.826, R2 0.211 [21.1%], p=0.031), skeletal muscle mass (β –2.150, R2 0.125 [12.5%], p=0.023), fasting glucose (β 1.273, R2 0.078 [7.8%], p=0.003), triglycerides (β 0.210, R2 0.014 [1.4%], p=0.008), and 6Mwt (β 0.183, R2 0.038 [3.8%], p=0.044). Conclusion: The CT order did not affect the magnitude of PEH, and body composition, cardiovascular, metabolic and physical condition outcomes can be predictors of their magnitude in individuals with morbidly obesity .